Variation in the Growth Traits of Plus Tree Progenies of Cedrus deodara (Roxb. Ex Lamb.) G. Don at Nursery Stage - Banyal, Savita K.; Sharma, Rajesh (Indian Forester, 2015)
Fifty two Plus trees were selected from different geographical areas to study genetic variation in growth traits amongst the progenies in the nursery. Analysis revealed significant variation between different plus trees for parameters under study i.e height, collar diameter and survival except germination (p = 0.05). Wide ranges in means were exhibited for germination (2-27%), height (4.6-21.1cm) and survival (1-16%). In all cases standard error was lower than their respective means. Germination showed positive and significant correlation with height (0.406) and survival (0.760). Plus tree located at Theog Forest Division was found to be best in all growth parameters.